A Clinical Rationale for Assessing the Impact of Childhood Sexual Abuse on Adjunctive Subcutaneous Esketamine for Treatment-Resistant Depression - Magalhães, Eduardo Jorge Muniz; Sarin, Luciana Maria; Del Sant, Lorena Catarina; Lucchese, Ana Cecília; Nakahira, Carolina; Tuena, Marco Aurélio; Puertas, Camila Brito; Rodovalho Fava, Victor Augusto; Delfino, Rodrigo Simonini; Surjan, Juliana; Steglich, Matheus Souza; Barbosa, Matheus Ghossain; et al. (Frontiers in Psychiatry, 2021)
Background: A history of child sexual abuse (CSA) is related to higher suicide rates and poor treatment outcomes in depressed adult patients. Twenty years after the first study investigating the effects of ketamine/ esketamine, on depression and suicide, there is a lack of data on the CSA effects on this emerging treatment. Here we assess the impact of CSA on adjunctive subcutaneous (SC) esketamine for treatment-resistant depression (TRD). Methods: A directed acyclic graphic (DAG) was designed to identify clinical confounders between CSA and esketamine predictors of response. The confounders were applied in a statistical model to predict depression symptoms trajectory in a sample of sixty-seven TRD outpatients. Results: The patient sample had a relatively high prevalence rate of CSA (35.82%). Positive family history of first-degree relatives with alcohol use disorder and sex were clinical mediators of the effects of esketamine in a CSA adult population. Overall, the presence of at least one CSA event was unrelated to esketamine symptom reduction. Conclusions: Unlike responses to conventional antidepressants and psychotherapy, CSA does not appear to predict poor response to esketamine.